Incidencia del virus de la tristeza de los cítricos en Venezuela - Plaza, G; Lastra, R; Martínez, J.E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Citrus tristeza virus was detected by ELISA in 53% of the citrus trees tested in Aragua, Carabobo and Yaracuy states Vinus-like particles with the shape and size of CTV were visualized by electron microscopy. The severe symptoms resulted in the decline and collapse of the affected trees High infestation with the ap/hid Toxoptera citricida K. was found in all surveyed areas.